Shock Wave Compression of Condensed Matter : A Primer - Forbes, Jerry W. (Heidelberg: Springer, 2012)
This book introduces the core concepts of the shock wave physics of condensed matter, taking a continuum mechanics approach to examine liquids and isotropic solids. The text primarily focuses on one-dimensional uniaxial compression in order to show the key features of condensed matter's response to shock wave loading. The first four chapters are specifically designed to quickly familiarize physical scientists and engineers with how shock waves interact with other shock waves or material boundaries, as well as to allow readers to better understand shock wave literature, use basic data analysis.
Includes bibliographical references and index.
Keywords: Condensed matter; Shock waves; Condensed matter; Shock waves